The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/cncr.22766
|View full text |Cite
|
Sign up to set email alerts
|

Virtual microscopy for cytology proficiency testing: Are we there yet?

Abstract: The current results confirmed the feasibility of VM for proficiency tests with 2 main problems noted. First, primary screeners had difficulties meeting the mandatory time allocation; however, with increased familiarity with the software, the screening times decreased. Second, the 3-dimensional nature of certain lesions made them difficult to interpret even on monolayered, liquid-based preparations. Creation of a more user-friendly software interface and better methods to capture depth of focus should make this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…The visual expertise learned by radiologists is an example of a search-related task, in which the radiologist identifies visual "targets" in an image containing both expected and "distractor" elements (Wen et al, 2016;Wolfe et al, 2015). Screening tests, both in radiology and pathology, are generally performed using a visual search model (Stewart et al, 2007;Wolfe, 1995). In this visual task, search is required because everything in the visual field cannot be identified and processed simultaneously.…”
Section: Search-related Expertisementioning
confidence: 99%
“…The visual expertise learned by radiologists is an example of a search-related task, in which the radiologist identifies visual "targets" in an image containing both expected and "distractor" elements (Wen et al, 2016;Wolfe et al, 2015). Screening tests, both in radiology and pathology, are generally performed using a visual search model (Stewart et al, 2007;Wolfe, 1995). In this visual task, search is required because everything in the visual field cannot be identified and processed simultaneously.…”
Section: Search-related Expertisementioning
confidence: 99%
“…Pilot results for scanning cytology slides (both conventional and thin layer techniques) appeared not to provide satisfactory results so this was not further pursued. This was mainly because multiple focus planes are needed for most cytological cases to obtain wellfocused cells [13].…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13] Some WSI scanners are capable of composing a three-dimension-like image by using multifocus frame images, and others can create a multilayer scanning image, which, for example, are stacked 10 layers each 2 lm apart along the z-axis. 13 Indeed, Dee et al 12 have reported the three-dimensional WSI system was useful for the education and testing of cervical cytology.…”
Section: Discussionmentioning
confidence: 99%